Association between hyperglycemia and organ dysfunction in shock patients - Sheila Noberta; Silvia Triratna; Aditiawati Aditiawati; Syarif Husin (Indonesian Pediatric Society Publishing House, 2013)
Background Hyperglycemia is an important marker of both poor clinical outcomes and high mortality rate in critically ill patients. Glucose toxicity results in cell damage that leads to organ dysfunction. Objective To evaluate for an association between hyperglycemia and the incidence of organ dysfunction in shock patients. Methods This cross-sectional study was conducted in the pediatric intensive care unit (PICU) of Dr. Moh. Hoesin Hospital, Palembang from June to November 2011. Subjects were consecutively-enrolled, shock patients without a history of diabetes mellitus. Illness severity and organ dysfunction were determined by pediatric risk of mortality (PRISM) III score and pediatric logistic organ dysfunction (PELOD) scores, respectively. Hyperglycemia was defined as a blood glucose level 2: 110 mg/dL. Statistical analysis was performed with SPSS version 15. Results Mean age of subjects was 2.30 (SD 2.93) years. Mean PRISM III score was 15 .11 (SD 5 .63). Prevalence of hyperglycemia was 80.0%. Mean glucose level was 179.51 (SD 86.84) mgldL. Mean PELOD score was 16.02 (SD 13.87). Organ dysfunction was observed in 86.7% of subjects. The most common organ dysfunction observed in our subjects was liver dysfunction (73.3%). There was a significant association between hyperglycemia and organ dysfunction (OR43.750;95%CI 4.036 to474.252, P=0.001). The blood glucose level cutoff points indicative of organ dysfunction, PRISM III score 2: 8, and PELOD score 2: 20.5 were 114.5 mg/ dL, 129 mgldL, and 166 mg/dL, respectively. Conclusion There is an association between hyperglycemia and organ dysfunction. The upper limit blood glucose level indicative of organ dysfunction is 114.5 mg/dL. A glucose level of 129 mgldL may be considered to be a warning to start blood glucose monitoring. A level above 166 mgldL may be used to indicate the necessity of starting insulin therapy intervention.